Cerebral Blood Flow Alterations in Pain-Processing Regions of Patients with Fibromyalgia Using Perfusion MR Imaging - Foerster, B.R.; Petrou, M.; Harris, R.E.; Barker, P.B.; Hoeffner, E.G.; Clauw, D.J.; Sundgren, P.C. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Widespread pain sensitivity in patients with FM suggests a CNS processing problem. The purpose of this study was to assess alterations in perfusion as measured by DSC in a number of brain regions implicated in pain processing between patients with FM and healthy controls. MATERIALS AND METHODS: Twenty-one patients with FM and 27 healthy controls underwent conventional MR imaging and DSC. For DSC, 12 regions of interest were placed in brain regions previously implicated in pain processing. rCBF values were calculated for each region of interest. Subjects answered mood/pain coping questionnaires and underwent clinical/experimental pain assessment. RESULTS: There were significant correlations between the thalamic rCBF values and the pain-control beliefs of FM subjects. The strength of the relationship between clinical pain measures and thalamic rCBF values increased after adjusting for pain-control beliefs. There was a significantly different distribution pattern of rCBF values across various brain regions between the FM group and the healthy controls. There was a lower degree of correlation in the FM group between the thalamic rCBF values and the other brain regions relative to the healthy controls. CONCLUSIONS: Significant correlations were found between thalamic rCBF values and pain belief values. These data suggest that there are baseline alterations of brain perfusion in patients with FM. rCBF values of the thalami exhibited lower correlations with respect to other brain regions thought to be involved in pain processing compared with those in healthy controls. ANOVAanalysis of varianceBPCQ-INTBeliefs about Pain Control Questionnaire-InternationalCBFcerebral blood flowCES-DCenter for Epidemiological Studies Depression ScaleCNScentral nervous systemCSQ-CATCatastrophizing Component of the Coping Strategies QuestionnaireDSCdynamic susceptibility-weighted contrast-enhanced perfusion MR imagingEPIecho-planar imagingFMfibromyalgiafMRIfunctional MR imagingPETpositron-emission tomographyrCBFrelative cerebral blood flowSEspin-echoSPECTsingle-photon emission tomographySTPISpielberger’s Trait Personality InventoryVASvisual analog scale